High sensitivity differential scanning calorimeter (HSDSC) technique for assaying ginger oleoresin - Noor Azlan, Morad; Abd. Aziz, Mustafa Kamal (Universiti Teknologi Malaysia, 2006)
The purpose of this study is to find a simplified method of quantifying and qualifying of products in particular ginger oleoresin. This is in line with the current trend of using natural products to replace synthetic products in medication, supplements and pharmaceuticals. Currently, the methods of quantifying and qualifying are rather tedious involving sample preparation and analysis which could comprise of a series of analytical technique. This may take days before the composition of a mixture can be confirmed. The propose method uses HSDSC or high sensitivity differential scanning calorimeter. This method is fast, requires no sample preparation and only a small quantity of sample is required. For the analysis, the method has been proven to be acceptable in identifying the purity of samples. The purity of 6-gingerol sample, a major component in ginger oleoresin can be identified using HSDSC. The purity of other ginger oleoresin can also be found using this technique. The method is advantageous over the conventional GC methods which is time consuming. The use of HSDSC to quantify ginger oleoresin however, is not conclusive. The method can only indicate that 6-gingerol is one of the main components but fail to give the exact amount. HSDSC is not capable of identifying the individual components in ginger oleoresin. The conventional method of quantifying ginger oleoresin sample using GC, HPLC and TLC is still required.